Giải bài 5 với những yêu cầu như trên

Question

Giải bài 5 với những yêu cầu như trên
giai-bai-5-voi-nhung-yeu-cau-nhu-tren

in progress 0
Sapo 12 months 2020-11-28T20:17:14+00:00 1 Answers 45 views 0

Answers ( )

    0
    2020-11-28T20:19:10+00:00

    Giải thích các bước giải:

    Ta có:

    \(\begin{array}{l}
    a,\\
    DKXD:\,\,\,\left\{ \begin{array}{l}
    x \ge 0\\
    x – 1 \ne 0\\
    x + 2\sqrt x  + 1 \ne 0
    \end{array} \right. \Leftrightarrow \left\{ \begin{array}{l}
    x \ge 0\\
    x \ne 1
    \end{array} \right.\\
    b,\\
    P = \left( {\dfrac{{\sqrt x  – 2}}{{x – 1}} – \dfrac{{\sqrt x  + 2}}{{x + 2\sqrt x  + 1}}} \right).\dfrac{{{{\left( {1 – x} \right)}^2}}}{2}\\
     = \left( {\dfrac{{\sqrt x  – 2}}{{\left( {\sqrt x  – 1} \right)\left( {\sqrt x  + 1} \right)}} – \dfrac{{\sqrt x  + 2}}{{{{\left( {\sqrt x  + 1} \right)}^2}}}} \right).\dfrac{{{{\left( {x – 1} \right)}^2}}}{2}\\
     = \dfrac{{\left( {\sqrt x  – 2} \right)\left( {\sqrt x  + 1} \right) – \left( {\sqrt x  + 2} \right)\left( {\sqrt x  – 1} \right)}}{{\left( {\sqrt x  – 1} \right){{\left( {\sqrt x  + 1} \right)}^2}}}.\dfrac{{{{\left( {\sqrt x  – 1} \right)}^2}.{{\left( {\sqrt x  + 1} \right)}^2}}}{2}\\
     = \dfrac{{\left( {x – \sqrt x  – 2} \right) – \left( {x + \sqrt x  – 2} \right)}}{{\left( {\sqrt x  – 1} \right){{\left( {\sqrt x  + 1} \right)}^2}}}.\dfrac{{{{\left( {\sqrt x  – 1} \right)}^2}.{{\left( {\sqrt x  + 1} \right)}^2}}}{2}\\
     = \dfrac{{ – 2\sqrt x }}{1}.\dfrac{{\sqrt x  – 1}}{2}\\
     =  – \sqrt x \left( {\sqrt x  – 1} \right)\\
    c,\\
    P =  – \sqrt x \left( {\sqrt x  – 1} \right)\\
     =  – \left( {x – \sqrt x } \right)\\
     =  – \left( {x – \sqrt x  + \dfrac{1}{4}} \right) + \dfrac{1}{4}\\
     = \dfrac{1}{4} – {\left( {\sqrt x  – \dfrac{1}{2}} \right)^2} \le \dfrac{1}{4},\,\,\,\forall x \ge 0,\,\,x \ne 1\\
     \Rightarrow {P_{\max }} = \dfrac{1}{4} \Leftrightarrow {\left( {\sqrt x  – \dfrac{1}{2}} \right)^2} = 0 \Leftrightarrow \sqrt x  = \dfrac{1}{2} \Leftrightarrow x = \dfrac{1}{4}\\
    d,\\
    0 < x < 1 \Rightarrow 0 < \sqrt x  < 1\\
     \Rightarrow \sqrt x  – 1 < 0\\
     \Rightarrow \sqrt x .\left( {\sqrt x  – 1} \right) < 0\\
     \Leftrightarrow  – \sqrt x .\left( {\sqrt x  – 1} \right) > 0\\
     \Leftrightarrow P > 0
    \end{array}\)

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )